Islam and politics: political attitudes of the elites in Muhammadiyah 1998-2010 - Ridho Al-Hamdi (IAIN Salatiga, 2013)
This study examines the roles of political elites in the Muhammadiyah in facingthe dynamics Muslim politics in post New Order regime. There are three issuesdiscussed: the emergence of Islamic political parties, the desire to implementthe Jakarta charter as a state ideology, and the rise of terrorism. The result ofthe study demonstrated that there are four variants of the political attitudes ofthe elites in Muhammadiyah in post-New Order regime: 1) transformative-ideal-istic; 2) moderate-idealistic, 3) realistic-critical, and 4) accommodative-prag-matic. The variations are deeply influenced by two main factors: the sociologicalbackground and organizational factor.Penelitian ini menguji peran elit politik dalam Muhammadiyah dalam menghadapidinamika politik Muslim pada era rezim pasca Orde Baru. Ada tiga isu yangdibahas: munculnya partai-partai politik Islam, keinginan untuk melaksanakanPiagam Jakarta sebagai ideologi negara, dan munculnya terorisme. Hasil penelitianmenunjukkan bahwa ada empat varian sikap politik para elite di Muhammadiyahpada era rezim pasca-Orde Baru: 1) transformatif-idealis; 2) moderat-idealis, 3) realistis-kritis, dan 4) akomodatif-pragmatis. Variasi ini sangat dipengaruhioleh dua faktor utama, yaitu latar belakang sosiologis dan faktor organisasi.